The Benefits of Ultrasonic Waves on Therapy: A Review of Literature - Ahmad Mukhlis Shobari; Maimon Sumo; Rohmatul Aini; Ussisah Sulistiawati; Luaini (PT. PENERBIT TIGA MUTIARA, 2024)
Physical fitness is a very important part of everyday life and almost everything that’s done depends on the physical member. In order to function properly, it is essential for us to maintain physical health so as not to cause problems and risk illness. In addition to the illness caused by physical activity, it can also be caused by age actors. In the field of health continues to undergo rapid development, one of the breakthroughs that has been used is the use of ultrasonic waves. Ultrasonic waves are the result of mechanical vibrations produced by the movement of isolated molecules in their diffusion media. If tissues receive ultrasound waves, the impact includes biological effects, mechanical effects and thermal effects. Some of the findings that have been established are the application of ultrasound waves to therapies in cases that appear on physical limbs. On this article aims to be able to contribute in the field of health so that it is easier to develop the use of ultrasonic therapy. This article is compiled using a literature review method taken from the references that have been collected. Of all the references collected, ultrasonic waves are used as therapies for some physical function problems. This therapy also collaborates with several paractic methods of health to address the existing problems. Therapy using ultrasonic modality has been shown to reduce pain, muscle cramps and minor injuries. It can be concluded that ultrasound therapy can help deal with patients suffering from disorders in their physical bodies, either to reduce pain or during the recovery process.